2017
DOI: 10.17509/ijal.v7i1.6864
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Gap Between Korean University Students’ Grammatical Awareness and Perception

Abstract: Despite the consistent emphasis on grammar instruction in English classrooms in South Korea, studies regarding grammar instruction have not yet been extensively conducted. The present study aims to discover the gap between learners' grammatical awareness and their perception of major grammatical items. A total of 60 EFL learners from two local universities in South Korea participated in the study and were divided into two groups, a high-level and a low-level group. A set of tests was utilized to examine learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This is indicated by the highest mean score if M=0.84 as shown in Table 3. This result is further supported by similar findings by Han and Kim (2017), claimed that learners have low proficiency level in grammar. Furthermore, some students did not know the correct grammatical features and this is due to their lack of knowledge and grammatical competency (Refnita,2014).…”
Section: B) Language Skill Areassupporting
confidence: 86%
“…This is indicated by the highest mean score if M=0.84 as shown in Table 3. This result is further supported by similar findings by Han and Kim (2017), claimed that learners have low proficiency level in grammar. Furthermore, some students did not know the correct grammatical features and this is due to their lack of knowledge and grammatical competency (Refnita,2014).…”
Section: B) Language Skill Areassupporting
confidence: 86%
“…Despite the high importance of having grammatical awareness among English learners, in fact, many students still have lack of grammatical awareness in learning English. In the line with this, Han and Kim (2017) claimed that EFL learners have lack of grammatical awareness and they have a low proficiency level. Some students did not know the correct grammatical features due to lack of knowledge and grammatical competency (Refnita, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Some researchers had already conducted similar studies to our current study. For example, Han and Kim (2017) who found that there was a significant difference in score of tense, article, and voice for grammatical awareness between high level and low-level groups. Both of groups had a high score for category of voice while they had low scores for vocabulary and morphology and perceived difficulties of articles and voice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the local university instructors have observed that first-year tertiary students, after 12-14 years of basic education and exposure to the English language, still have difficulty generating rich ideas or expressing their thoughts. Teaching and helping students reduce mistakes is crucial [4]. Thus, Lewis and Ferretti [5] indicated that writing is one of the lowest priorities in many English teachers' classrooms [6].…”
Section: Introductionmentioning
confidence: 99%